The two-continuum mechanics of dielectrics as a basis of the theory of piezoelectricity and electrostriction - Khoroshun, L. P. (International applied mechanics, 2008)
The paper proposes a new principle for setting up the theory of coupled dynamic electroelasticity of dielectrics that have piezoelectric and electrostrictive properties. The theory is based on the purely mechanical two-continuum description of dielectrics as a mixture of positive and negative charges coupled into neutral molecules or elementary cells. It is assumed that an elastic potential exists and that the partial stresses are in quadratically nonlinear dependence on the difference of the displacements of charges. Based on the definition of the polarization vector of an elementary dielectric volume and the electric field it generates, the equations of two-continuum mechanics are reduced to coupled dynamic equations for the macrodisplacements of neutral molecules and the electric-field intensity, which describe the piezoelectric and electrostrictive effects